Effect of Hadron Contamination on Dielectron Signal Reconstruction in Heavy Flavor Production Measurements - Daniel Kikoła (Advances in High Energy Physics)
Dielectron signal reconstruction is an important tool for heavy flavor measurements because of its trigger feasibility and its relatively straightforward particle identification process. However, in the case of time projection chamber detectors, some hadron contamination is unavoidable, even if additional means are used to improve the particle identification process. In this paper, we investigate the effects of hadron (protons, pions, and kaons) contamination on the dielectron signal reconstruction process in the measurement of J/ψ and electrons from heavy flavor hadron decays.